Preferensi Preferensi wisatawan mancanegara dalam pemilihan akomodasi di desa wisata nyuh kuning ubud, bali - ni made pande purwaningsih; Ni Putu Ratna Sari; Agung Sri Sulistyawati (Jurnal Kepariwisataan dan Hospitalitas, 2018)
The research report is entitled "Foreign Tourist Preferences in Accommodation Selection in Nyuh Kuning Tourism Village, Ubud". The purpose of this study is to determine the characteristics of tourists and know the preferences of foreign tourists in the selection of accommodation in the Tourism Village Nyuh Yellow. Indicators used in this research are location, facility, service, image, price, comfort, hygiene, health, promotion, and architecture. This research data obtained through observation, questionnaires, interviews and documentation. Determination of sampling technique is determined by incidental sampling technique to 100 foreign tourists. Data analysis techniques used are quantitative statistics (konjoin analysis) and supported by qualitative data with ten research variables. The results show that the most important attribute according to foreign tourists in the selection of accommodation in Nyuh Kuning Tourism Village is the attribute of comfort. In addition, the result of a conjoint analysis of the preferences of foreign tourists in accommodation selection is a friendly service, a location close to the crowded center of Nyuh Kuning, an accommodation facility consisting of air conditioning, TV, swimming pool, wifi, hot and cold water, accommodation rates more than Rp. 800,000, accommodation with traditional architecture, daily cleaned rooms, accommodations rated more than 8, facets of health for relaxation, and promotions with free yoga. The suggestion in this research is that local people must provide identity for the accommodation they have. Second, the accommodation is expected to be more attractive in marketing the accommodation provided. The third suggestion is to make attractive promotions and offers for tourists. The final suggestion, it is recommended for the government and management to review and rearrange the existing accommodation policy.